2018
DOI: 10.1111/resp.13377
|View full text |Cite
|
Sign up to set email alerts
|

Virtual bronchoscopic navigation as an aid to CT‐guided transbronchial biopsy improves the diagnostic yield for small peripheral pulmonary lesions

Abstract: Combining VBN with CT-TBB significantly improved the diagnostic yield for small PPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 25 publications
0
27
1
Order By: Relevance
“…reported that concomitant use of VBN in bronchoscopy of 3 cm or smaller peripheral lesions using a 2.8‐mm ultrathin bronchoscope and X‐ray fluoroscopy increased the diagnostic yield from 59.9% to 67.1%. However, the increase was not significant and the diagnostic yield of lesions located in the peripheral one‐third of the lung was significantly improved in sub‐analysis, as also reported in the current study …”
contrasting
confidence: 62%
See 4 more Smart Citations
“…reported that concomitant use of VBN in bronchoscopy of 3 cm or smaller peripheral lesions using a 2.8‐mm ultrathin bronchoscope and X‐ray fluoroscopy increased the diagnostic yield from 59.9% to 67.1%. However, the increase was not significant and the diagnostic yield of lesions located in the peripheral one‐third of the lung was significantly improved in sub‐analysis, as also reported in the current study …”
contrasting
confidence: 62%
“…In sub‐analysis of the data collected by combination with EBUS‐GS, VBN significantly increased the diagnostic yield of CT‐BS‐positive lesions smaller than 2 cm from 70.7% to 94.6%, although these findings cannot be directly compared with that of the present study . Furthermore, Oki et al .…”
mentioning
confidence: 99%
See 3 more Smart Citations